Morphometric studies of periodontal structures during opioid exposure at the end of six and eight weeks. - Fik, V. B.; Chelpanova, I. V.; Paltоv, E. V. (Морфологія / Morphologia / Morfologìâ, 2019)
Background. Opioid analgesics are characterized by both analgesic and narcogenic effects. Periodontal tissues occupy a leading place in the pathology of oral organs, since they clearly reflect the impact of negative factors, making the study of pathological changes in periodontal drugs with long-term exposure to narcotic substances an urgent problem. Objective. To study the morphometric parameters of the structural components of periodontal opioid exposure for six and eight weeks in the experiment. Methods. The study material consisted of 26 white male rats weighing 160 g, 4.5 - 6.5 months of age. Animals were divided into 3 groups. The first group was intact, in the second group of rats administered intramuscular nalbuphine at a dose of 0.252 mg / kg for 5 and 6 weeks, the dose was increased to 0.260 mg / kg in the third group (7 and 8 weeks). For morphometric studies, histological sections of the gums from fragments of the mandible of rats were used. The analysis of the results of the morphometric study and the statistical processing of the data were performed according to generally accepted statistical methods. Results. Morphometrically, it was found that with the action of an opioid analgesic during the six and eight weeks of the experiment, the average thickness of the epithelium of the gums and height of the connective tissue papillae decreased significantly. The average values of the periodontal width are almost unchanged. In connective tissue, vascular disorders are observed, the average lumen diameter of venules, hemocapillaries and arterioles increases. Conclusion. The results of morphometric studies indicate an increase in pathological changes in the dynamics during the six-week and eight-week opioid exposure, which is a consequence of significant disturbances in the trophic component of periodontal components, the development of stagnation and the progression of tissue hypoxia.